2014
DOI: 10.1002/cphc.201300957
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Enhanced Hydration of Aqueous Electrolyte Solution in Hydrophobic Carbon Nanotubes to Maintain Stability

Abstract: An understanding of the structure and behavior of electrolyte solutions in nanoenvironements is crucial not only for a wide variety of applications, but also for the development of physical, chemical, and biological processes. We demonstrate the structure and stability of electrolyte in carbon nanotubes using hybrid reverse Monte Carlo simulations of X-ray diffraction patterns. Hydrogen bonds between water are adequately formed in carbon nanotubes, although some hydrogen bonds are restricted by the interfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…18,46,50,51 Although the different parameters produced somewhat different physical properties, the above potential parameters also described experimental properties such as structures well. Furthermore, our preceding studies indicated that the structures of electrolyte and water in confined carbon nanopores using the CEMC simulations agreed well with the experimental structures, 38,52 although the comparison of dynamic properties has been inadequate. In this study, a simple point charge model was adopted to evaluate dynamic properties of electrolytes.…”
Section: ■ Methodssupporting
confidence: 53%
See 3 more Smart Citations
“…18,46,50,51 Although the different parameters produced somewhat different physical properties, the above potential parameters also described experimental properties such as structures well. Furthermore, our preceding studies indicated that the structures of electrolyte and water in confined carbon nanopores using the CEMC simulations agreed well with the experimental structures, 38,52 although the comparison of dynamic properties has been inadequate. In this study, a simple point charge model was adopted to evaluate dynamic properties of electrolytes.…”
Section: ■ Methodssupporting
confidence: 53%
“…This indicates that the extent of hydrogen bonding was significantly decreased for those water molecules involved in hydration shell formation. 37,38 The hydrogen bonding numbers recovered to the overall average value at the charge-reversal processes. This indicated that hydration shell water molecules reformed their hydrogen bonding network just before release from the hydration shell.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…CNTs are only at the liquid–air interface, which is the major difference from the dip-coating method. By making full use of the hydrophobicity of CNT, thickness control of the CNT is possible by matching the target substrate surface chemistry . By repeated dipping, lifting, and drying, >100 layers can be put on quartz or glass substrates.…”
Section: Preparation Of Transparent Cnt Filmsmentioning
confidence: 99%